Comparative evaluation of the decrease of visual functions and changes of morphometric parameters of macular area with the patients with post-thrombotic macular edema - I. P. Shurygina; E. V. Kabardina; M. K. Shulikova; Y. A. Borzilova (Кубанский научный медицинский вестник, 2014)
In this work comparative evaluation between the degree of the decrease of visual acuity and the data of morphometric research of the macular area (thickness of the central area of retina and the volume of the macular area) with the patients with macular edema developed against the backdrop of thrombosis of top temple branch of the central vein of retina was made. The data received make it possible to And the tactics of the future treatment and prophylaxis therapy of the patients with post-thrombotic retinopathy.